Position statement of the Spanish Society of Paediatric Infectious diseases on the diagnosis and treatment of Mycoplasma pneumoniae infection - Walter Alfredo Goycochea-Valdivia; Josefa Ares Alvarez; Antonio José Conejo Fernández; Ana Belén Jiménez Jiménez; Irene Maté Cano; Teresa de Jesús Reinoso Lozano; Carlos Rodrigo Gonzalo de Liria (Elsevier, 2024)
Mycoplasma pneumoniae (M. pneumoniae) is a bacterium with particular characteristics that give rise to a broad clinical spectrum, being respiratory infection the most frequent presentation. Infection by M. pneumoniae occurs in cyclical epidemics, and paediatricians in Spain have noticed an increase in cases since January 2024, establishing hospital registers to collect surveillance data (as it is not a notifiable disease in Spain). The diagnosis of infection by M. pneumoniae is made through serological testing and/or the detection of genetic material by means of polymerase chain reaction (PCR). Neither methods can differentiate between colonization and active infection, so a precise diagnosis is not possible and testing should only be requested in the case of high clinical suspicion. The role of antibiotherapy in infection by M. pneumoniae in its different clinical variants is not well defined. Most infections are self-limiting and mild, and there is insufficient evidence to support the use of antibiotherapy in these cases. Antibiotic treatment is justified in patients with risk factors for the development of severe disease (Down syndrome, anatomical or functional asplenia, immunosuppression), in hospitalized patients with respiratory infection and in patients with moderate or severe extrapulmonary forms. Taking into account aspects concerning the rational use of antimicrobials, the treatment of choice would be clarithromycin, with azithromycin as an alternative, reserving the use of doxycycline and levofloxacin for cases of antimicrobial resistance and/or infections of the central nervous system. Resumen: Mycoplasma pneumoniae (MP) es una bacteria con características peculiares que produce un amplio espectro de manifestaciones clínicas siendo la infección respiratoria la más frecuente de ellas. Se presenta en epidemias cíclicas, percibiendo los pediatras en España un incremento de casos desde enero del 2024, poniéndose en marcha registros hospitalarios (no es una enfermedad con declaración obligatoria en nuestro medio). El diagnóstico de la infección por MP se realiza mediante la determinación de serologías y/o la detección de material genético mediante reacción en cadena de polimerasa (PCR). Ambas son incapaces de diferenciar la colonización de la infección activa, por lo cual el diagnóstico preciso no es posible y deben solicitarse sólo en caso de alta sospecha clínica. El papel del tratamiento antibiótico en la infección por MP en sus diferentes variantes clínicas no está bien definido. La mayoría de las infecciones son autolimitadas y leves, sin evidencia suficiente en favor de la antibioterapia en estos casos. El tratamiento antibiótico estaría justificado en pacientes con factores de riesgo para desarrollo de formas graves (Síndrome de Down, asplenia anatómica o funcional, inmunodepresión), en pacientes hospitalizados con infección respiratoria y en pacientes con formas extrapulmonares moderadas o graves. Considerando aspectos referentes a la optimización del uso de antimicrobianos, el tratamiento de elección sería claritromicina, siendo alternativo el uso de azitromicina; y reservando el uso de doxiciclina y levofloxacino para los casos de resistencias antimicrobianas y/o infecciones del sistema nervioso central.